ChemInform Abstract: Efficient Synthesis of N‐Alkylated α, β‐Unsaturated Ketonitrones via Cu‐Catalyzed Rearrangement. Issue 7 (29th January 2015) - Nakamura, Itaru; Onuma, Toshiki; Kanazawa, Ryo; Nishigai, Yuki; Terada, Masahiro
Abstract The title compounds are efficiently synthesized from propargyloxyamines.